Fe–N–C electrocatalysts in the oxygen and nitrogen cycles in alkaline media: the role of iron carbide. Issue 47 (20th October 2021) - Burshtein, Tomer Y.; Aias, Denial; Wang, Jin; Sananis, Matan; Farber, Eliyahu M.; Gazit, Oz M.; Grinberg, Ilya; Eisenberg, David
Abstract : Iron carbide, a ubiquitous component of Fe–N–C material, is found to be electrocatalytically inactive towards hydrazine oxidation and oxygen reduction in alkaline media, through a combined experimental and computational study. Abstract : Fe–N–C electrocatalysts hold a great promise for Pt-free energy conversion, driving the electrocatalysis of oxygen reduction and evolution, oxidation of nitrogen fuels, and reduction of N2, CO2, and NO x . Nevertheless, the catalytic role of iron carbide, a component of nearly every pyrolytic Fe–N–C material, is at the focus of a heated controversy. We now resolve the debate by examining a broad range of Fe3 C sites, spanning across many typical size distributions and carbon environments. Removing Fe3 C selectively by a non-oxidizing acid reveals its inactivity towards two representative reactions in alkaline media, oxygen reduction and hydrazine oxidation. The activity is assigned to other pre-existing sites, most probably Fe–N x . DFT calculations prove that the Fe3 C surface binds O and N intermediates too strongly to be catalytic. By settling the argument on the catalytic role of Fe3 C in alkaline electrocatalysis, we hope to spur innovation in this critical field.